Morphology of secretory structures and essential oil composition in Mentha cervina L. from Portugal - Rodrigues, Leandra (2008)
ABSTRACT: Mentha cervina L. is an aromatic plant that is traditionally used in the Alentejo region of Portugal to flavour food dishes and for the medicinal properties of the essential oil produced in its glandular trichomes. The morphology and distribution of the secretory structures of 20 populations was studied by light and scanning electron microscopy and revealed a great similarity in the type and distribution of glandular and non-glandular trichomes. In addition, two populations were surveyed at different stages of their life cycles. This showed that both maximum trichome density and maximum filling capacity of the glandular trichomes are attained early on. The GC and GC–MS chemical analyses showed that pulegone (62–80%), isomenthone (3–18%) and limonene (3–7%) are the main components of M. cervina essential oils. Cluster analysis of the identified essential oil components revealed a major chemical consistency between the 20 populations evaluated